Study of mechanical behavior of ultra - high performance concrete (UHPC) reinforced with hybrid fibers and with reduced cement consumption - Christ, R.; Pacheco, F.; Ehrenbring, H.; Quinino, U.; Mancio, M.; Muñoz, Y.; Tutikian, B. (Revista Ingeniería de Construcción, 2019)
This article evaluated mechanical behavior of ultra-high performance concrete (UHPC) reinforced with hybrid steel and polypropylene fibers, with cement consumption of 250 kg/m³ and application of confining pressure in fresh state. The consistency of the mixture was analyzed, as well as mechanical properties of compressive strength, flexural strength and toughness. The percentages of hybridization were 50 to 100% of metal fibers and 0 to 50% of polypropylene fibers. Results showed that the compressive strength of the composite was 180 MPa (26100 psi), despite its low cement consumption of 250 kg/m³ (2.08 lb/gal), with 80% steel fibers and 20% polypropylene fibers. The combination of fibers increased the mixture’s toughness. For the composition with 80% steel fibers and 20% polypropylene fibers, the strength for large deformations increased by 191% compared with the mixture with 100% steel fibers, pointing out the benefits of hybridization